The Role of Iranians in Istanbul in Publishing and Distributing Modernist and Constitutionalist Texts - Mohammad Hossein Sadeghi; Hassan Hazrati (پژوهش های تاریخی)
AbstractThis research aimed to investigate the role of Iranians in Istanbul in publishing and distributing modernist and constitutionalist texts, by discovering channels of communication between Iranian and Ottoman constitutionalists. Therefore, after presenting an outline of the Iranians of Istanbul, it explained the general coordinates of Istanbul (concerning the topic of the research) as the most important center of communication between Iranian and Ottoman constitutionalists and specified its place in the publication and distribution of Persian texts. Thereafter, focusing on Iranian printers or writers, as agents of publication and distribution of the aforementioned works, the role of these individuals in the production and transfer of works containing the idea of modernism and constitutionalism between Iran and the Ottoman Empire was investigated. It was found that these individuals, by being present in Istanbul and taking advantage of the facilities provided by this city; authored, translated, and published the aforementioned works. In the following, attention is focused on the activity centers of Iranians by mentioning places such as Valide Han and the Iranian School in Istanbul. The study explained their role and position in completing the chain of communication between Iranian and Ottoman constitutionalists. It showed that active Iranians in the Ottoman publishing industry published works containing the ideas of modernism and constitutionalism in centers such as Iranian Publishing Company (شرکت صحافیۀ ایرانیه) and Akhtar Printing Press (مطبعۀ اختر); and these works were delivered to Iranian and Ottoman audience through other centers such as bookstores, especially in the bookseller Bazaar (صحافلار چارشوسی). In addition to the intellectual nourishment of Istanbul, these works were also exported to other regions such as Iran and Iraq. Based on the research findings, it can be claimed that the constitutionalist Iranians in Istanbul, by communicating with their Iranian and Ottoman audiences, played an important role in promoting the idea of ​​constitutionalism in Iran and the Ottoman Empire. IntroductionAt the end of the 19th century and the early 20th century (14 A.H.), many Iranians migrated to Ottoman territories due to economic, political, and cultural reasons, with a significant number settling in Istanbul. This migration facilitated mutual influence between Iranians and Ottomans. Concurrently, amidst the rise of the constitutionalism movement in Iran, political conditions under Qajar despotism restricted political freedoms, prompting constitutionalist activists to migrate to the Ottoman Empire. Istanbul's proximity to Iran and its independence from Qajar influence made it an attractive destination. Despite political despotism and press censorship during the Ottoman Hamidian period, Iranian activists enjoyed relatively more freedom compared to their Ottoman counterparts. During their stay in the Ottoman Empire, these individuals engaged with various segments of the Ottoman society, including reformist politicians and constitutionalist intellectuals, and over forty years, played a pivotal role in exchanging experiences of reform and constitutionalism between Iranians and the Ottomans. During this period and with the expansion of constitutionalism, both the Ottoman Empire and Iran were significantly influenced by these movements.Constitutionalism in both countries significantly influenced each other. The presence of numerous Iranian constitutionalists in Istanbul, coupled with their active involvement in the Ottoman publishing industry, fostered a robust relationship between Iranian and Ottoman constitutionalists. Through interactions with Ottoman counterparts, these Iranians enhanced their political acumen and established channels to introduce new ideas, including constitutionalism, into Iran. Consequently, the constitutional processes in both nations mutually influenced each other. To this end, the present study investigated the role of Iranians in Istanbul in authoring, translating, printing, and distributing texts that laid the theoretical foundations for constitutionalism.Materials and MethodsThis research aims to provide a thick description of the publishing activities of Iranians in Istanbul regarding constitutionalism, employing a descriptive-analytical approach and drawing on primary sources such as travelogues, diaries, newspapers, archival documents, and Ottoman yearbooks. It focuses on activities such as authoring, publishing, and disseminating texts that encompass concepts of modernity and constitutionalism. Furthermore, the study examines how Iranian authors in Istanbul influenced the development of constitutionalism in both Iran and the Ottoman Empire through their publishing endeavors.Research FindingsThis research highlights Istanbul's pivotal role in the publication and distribution of Persian texts, fueled by a new wave of Iranian immigrants arriving from the second half of the 19th/13th century. Istanbul not only catered to the Ottoman audience but also supplied the publishing demands of intellectual environments in Iran, India, Central Asia, the Caucasus, and Europe. The extensive interactions among various Iranian groups in Istanbul played a crucial role in disseminating new political ideas, including constitutionalism, between Iran and the Ottoman Empire. This research, by focusing on the cultural and political activity centers of Iranians, showed their role and position in completing the chain of communication between Iranian and Ottoman constitutionalists. By paying attention to Iranian publishers in the Ottoman Empire, the study described how they played a role in the production and transmission of texts containing modernism and constitutionalism aspects.Although all texts containing the idea of constitutionalism were banned by the Ottoman government, Iranian publishers published these texts illegally and delivered them to Iranian and Turkish audiences through various channels. This study focuses on Iranian printers and authors who acted as publishers and distributors of these works. It explores their significant impact on the dissemination of such literature across Iran and the Ottoman Empire, highlighting their roles in authoring, translating, and publishing. Iranian publications, facilitated through institutions like the Iranian Publishing Company, the Akhtar Printing Press in Valide Han, and the Khorsheed Printing Press in Mahmoud Pasha, reached Iranian and Ottoman audiences through channels such as bookstores, notably in the Booksellers Bazaar. It should be noted that, contrary to the existing perception, the Iranian constitutionalists in Istanbul did not have complete comfort and freedom of action. In the suffocating atmosphere of Hamidian despotism, they acted with difficulty and in most cases secretly; however, they faced less sensitivity than their Ottoman counterparts. In addition to enriching intellectual discourse in Istanbul, these works were exported to regions including Iran and Iraq, furthering their influence beyond the city.Discussion of Results and ConclusionsAn examination of Istanbul's central position reveals its role as an intermediary hub for the exchange of written works such as books and newspapers during the periods of Iranian and Ottoman constitutionalism. Istanbul served as both an exporter and importer of various publications. Despite efforts by the despotic regime of Abdulhamid II to censor and prohibit works deemed detrimental to Ottoman interests, Iranian publishers in Istanbul played a crucial role in facilitating the transfer of books and newspapers between Iran and the Ottoman Empire. These publishers not only catered to intellectuals in other regions but also redistributed new intellectual products. The prohibitions imposed by Ottoman and Iranian authorities on these transfers were largely due to their concern that constitutionalist texts from both countries would influence the citizens of both nations. While the Ottoman government justified the ban on these texts for religious and political reasons, no document explicitly labeled these texts as containing constitutionalist ideas. However, given the context of the time, such "harmful" texts most likely opposed despotism and promoted liberalism or constitutional ideals.